Resolving Recent Economic Crisis Created by The Tariff War of US Through ‎Bibliometric Analysis of ContemporaryLeadership Style and Lord Rama’s Leadership to Achieve Sustainability - Takkar, Dr. Manali; Kumar, Dr. Sujit (International Journal of Accounting and Economics Studies, 2025)
This paper examines the ethical leadership of Lord Rama as portrayed in the Hindu epic, ‎Ramayana, and explores how his principles align with contemporary Economic policies at ‎the macro and micro levels, thereby leading to sustainability and peace. In the present-day world, which has ‎changed the shape and future of generations by making dramatic progress in the field of ‎technology, innovation, and inventions, the need for dynamic and skilled leaders is significant. ‎This paper provides a bibliometric analysis of the articles on contemporary leadership style by ‎examining 280 papers collected from Scopus and Web of Science databases from 2005 to 2024 ‎using the Biblioshiny package in R software and VOS Viewer to delineate influential aspects, ‎trend topics, themes, conceptual, intellectual, and social structure. The findings indicate ‎the relevance of Rama’s Leadership style adopted way back in the 7th to 4th century BCE in ‎the modern economy. Further, the study proposes how ancient values can inform sustainable and ‎responsible leadership today. It also provides the scope for further research concerning political, ‎cultural, gender, female-based, and transformational leadership.